Marine Isotope Stage 11c: An unusual interglacial. (15th May 2022) - Tzedakis, Polychronis C.; Hodell, David A.; Nehrbass-Ahles, Christoph; Mitsui, Takahito; Wolff, Eric W.
Abstract: Notoriety of the Marine Isotope Stage (MIS) 11c interglacial arises from its long duration, extending over two precessional cycles, high sea level, and persistence of high atmospheric CO2 concentrations. The strong climatic response is often considered paradoxical because it was attained under weak boreal summer insolation forcing, a function of an extended eccentricity minimum and of precession and obliquity being almost opposite in phase. Here, we trace the characteristics of MIS 11c and explore their most likely causes. MIS 11c was preceded by the largest Quaternary ice volume expansion of MIS 12, which ended with a long period of ice rafting and interhemispheric heat transfer. We suggest that the duration of MIS 12 and the size of ice sheets exceeded a critical threshold that triggered a deglaciation despite the weak insolation forcing. The weak forcing led to a slow but steady loss of ice volume, that was sufficient to allow ocean outgassing of CO2, but insufficient to raise sea level within a single precessional cycle. This gave rise to a prolonged interval with large residual ice sheets and high CO2 concentrations that is unique in the last 800, 000 years. The obliquity-precession antiphasing produced a weak boreal summer insolation minimum, skipping a glacial inception and leading to continued sea-level rise and high CO2 concentrations, sustained by carbonate compensation. Full interglacial conditions were achieved in the second precessional cycle, and the combined strength and length of the interglacial probably led to loss of some Greenland and Antarctic ice compared to other interglacials. While MIS 11c is highly unusual in many respects, these appear to be linked to each other through the very weak insolation forcing, which led to its extended duration, slow sea-level rise and stable CO2 concentrations through a cocktail of counteracting carbon cycle processes. Although some of these features are also encountered in other interglacials, their combination with strong interglacial intensity is unique to MIS 11c and this appears to be a function of the large MIS 12 ice sheets and the high CO2 concentrations from the beginning of the interglacial. Highlights: MIS 11c was one of the longest and strongest interglacials of the last 800 kyr. High sea level and CO2 concentrations were attained under weak insolation forcing. Critical size of ice sheets at 430 ka triggered deglaciation, but sea-level rise was slow. Presence of large residual ice sheets and high CO2 in the first part of MIS 11c. Precession and obliquity antiphasing led to prolonged warmth and high sea level.